The Impact of Changing Physicians on Compliance with Management of Myopia Progression - Schibli, Fabian; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2025)
Background The global incidence of high myopia is increasing, with projections indicating a rise from 3 to 10% of the global population by 2050. Effective treatment options exist to reduce myopia progression, but their success is contingent on patient adherence. This study assesses the impact of changes in treating physicians on adherence to therapy to control myopia progression.Patients and Methods This retrospective observational study analyzed data from the Myopia Clinic at the University Eye Hospital of Basel from 2020 to 2023. Adherence rates were compared between consultations with and without a change in the treating physician, as well as between resident and senior physicians. Statistical analysis was performed using unpaired t-tests and chi-squared tests.Results A total of 73 patients, with a mean age of 10.76 years, who had at least three axial length measurements were included. Overall, 84.79% of consultations adhered to the recommended treatment. A significantly higher nonadherence rate of 21.43% was observed in consultations following a change in physician, compared to 6.42% with physician stability (p = 0.0037). Nonadherence was also higher with resident physicians (18.31%) compared to senior physicians (8.70%; p = 0.0310). No significant difference in adherence was found between optical and medical treatment options (p = 0.6293). Age and gender did not significantly influence adherence.Discussion The study reveals a significant negative impact of physician changes on patient adherence in therapy to control myopia progression control. The findings emphasize the importance of consistent physician care, particularly in avoiding frequent rotations among resident physicians, in order to enhance treatment adherence. While the studyʼs limitations include a small sample size and single-center data, the results suggest that strategies to minimize changes in treating physicians could improve adherence outcomes.
Keywords: myopia; patient adherence; myopia progression management; physician continuity